Total and added sugars consumption in Argentina : their contribution to daily energy intake : results from Latin American Study of Nutrition and Health (ELANS) - Kovalskys, Irina (2019)
Fil: Kovalskys, Irina. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Escuela de Nutrición; Argentina